Operational process stability in pilot dry anaerobic digester of source-sorted organic fraction municipal solid waste - Zainal, Afifi; Harun, Razif; Yahya, Liyana; Idrus, Syazwani (John Wiley and Sons, 2024)
The organic fraction of municipal solid waste (OFMSW) is a major portion of solid waste in Malaysia, with 44.5% of the total waste being food waste-derived sources. This study investigates the performance of dry anaerobic digester (DAD) operation using the pilot dry anaerobic digester (PDAD), a plug flow reactor, in treating source-sorted organic fraction municipal solid waste (SS-OFMSW) for biogas production. A commercial Malaysian food waste (CMFW) sample has been used to represent SS-OFMSW. The anaerobic digestion was performed in a semi-continuous operation using a 15 m3 PDAD with organic loading rates (OLRs) ranging from .63 to 5.46 kg volatile solid (VS)/m3·day under mesophilic conditions. The maximum methane composition was achieved at 56.0% at OLR 5.17 kg VS/m3·day with specific methane production (SMP) of .57 m3·CH4/kg VSfed and gas production rate (GPR) 5.27 m3·gas/m3·digester·day. As indicated by a pH and alkalinity ratio, the PDAD system was stable ranging from pH 6.7 to 8.3, alkalinity ratio of .3 with an inclination of total ammonia nitrogen (TAN) up to 1056 mg/L. The SMP achieved is between 1.58 and .4 m3·CH4/kg VSfed and potentially to fuelled 475 MW commercial biogas plant fed by CMFW. The DAD deployment strengthened the circular economy and decarbonization initiatives.